EXPERIMENTAL STUDY ON EVALUATION OF CAVITATION AND WORKING PERFORMANCE OF MOSWELL AQUA 175 CENTRIFUGAL PUMP ON SERIES SERIES WITH DEBIT VARIATIONS - Bagas, Putra; Faizin, Ahmad Khairul (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
Centrifugal pump is commonly used in industry. Centrifugal pumps work by converting mechanical energy into pressure and kinetic energy. In centrifugal pumps, cavitation or decrease in pump performance due to bubbles in the pump cavity is possible. The impact of cavitation is possibly damage the impeller, reduce efficiency, and increase maintenance costs. In this study, the evaluation of cavitation and the calculation of pump and head efficiency are important things to be carried out in assessing the performance of the pumping system. The pump used in this study is a Moswell Aqua 175 centrifugal pump. The piping systems are arranged in series. The variable used is flow discharge with 10 variations. The maximum flow discharge of the Moswell Aqua 175 pump is 60.7 L/min as the highest variation and the lowest variation is 9.4 L/min. The research began by compiling a series of piping systems and then draining water on the pump by varying the discharge of water flow. The calculation in this study is to find the NPSH-A (Net Positive Suction Head – Available) value, head, and pump efficiency. The results of the study showed that the NPSH-A value was above 8m and greater than the NPSH-R (Net Positive Suction Head – Required) value of 3m which means cavitation did not occur in the pump. The head value and efficiency of the pump increase significantly as the flow discharge variation increases. At the highest water discharge, which is 60.7 L/min, a head value of 9.677m was obtained with a pump efficiency of 37.93%. This shows that centrifugal pumps work more efficiently at higher flow rates.